Fixing Failed States: an unconventional agenda based on lessons learned from the afghan fiasco - Serge Michailof (Fondation pour les études et recherches sur le développement international (FERDI), 2010)
For more than forty years, developing countries have experienced a series of wars and armed conflicts. These have essentially been internal conflicts like in Afghanistan, Cambodia, Rwanda, and Colombia, although they have had a strong tendency to involve neighboring countries.Many of these conflicts have affected countries without significantly upsetting the ability of the government to continue functioning. This is currently the case for example in the Ivory Coast, even though, paradoxically, this country's public administration cannot measure up to what it was thirty years ago. In these cases, reconstruction is essentially an issue of political stabilization and 'good' policies facilitating private investment recovery. In these situations, the Official Development Assistance (ODA) plays its traditional role: its goal is to enable these countries — some of which, like the Ivory Coast, have lost several decades in terms of development — to make up for lost time.
Keywords: F35; F52; F42; H11; K32; P48; 330